How Can Servant Leadership Promote Employees’ Voice Behavior? A Moderated Chain Mediation Model - Chen, Hao; Wang, Liang; Li, Jingya (Frontiers in Psychology, 2022)
Purpose: Based on Social Exchange Theory, this paper constructs and tests the mediation model of servant leadership on employees' voice behavior through psychological security and error learning ability, and discusses the moderation role of work autonomy in the model. Design: This research takes 424 employees and their direct superiors as the research objects, then conducts a paired survey at three time points. The empirical data is analyzed by mplus7.4 software. Findings: The results are shown as follows: servant leadership is positively correlated with employees’ voice behavior; but psychological security and error learning ability play a partial mediation role in the positive impact of servant leadership on employees' voice behavior;and psychological security and error learning ability play a chain mediation role in the positive impact of servant leadership on employees' voice behavior;besides,work autonomy moderates the chain mediation path by enhancing the positive impact of servant leadership on psychological security, that is, the higher the employees' work autonomy is, the stronger the positive impact of servant leadership on psychological security is, and the stronger the chain mediation effect of psychological security and error learning ability between servant leadership and employees’ voice behavior is. Practical implications: Managers should abandon the traditional "command and control" management mode, then focus on the servant leadership behavior style, improve employees' psychological security through a comfortable and independent working environment. Besides, managers should establish a good error learning atmosphere mechanism, appropriately authorize employees at work, give them a certain degree of work autonomy, increase employees' work flexibility, and encourage employees to provide positive voice for the development and progress of the organization. Origin/value: From the perspective of Social Exchange, this study more comprehensively discusses the internal action path of the impact of servant leadership on employees' voice behavior, enriches the antecedent variables of employees' voice behavior, expands the existing research on the mediation mechanism of servant leadership, deepens the understanding of the efficiency mechanism of servant leadership, and has enlightenment significance for managers to better stimulate employees' voice.